Análise de Sensibilidade de Anemômetros a Temperatura Constante Baseados em Sensor Termo-resistivo - Gabriel, Michel Valença (2004)
In this work we present a study on the sensitivity of anemometers based on thermoresistive sensors heated to a constant temperature. The configurations that makes the thermoresistive sensor heated to a constant temperature are composed of a Wheatstone bridge using a feedback operational amplifier. The substitution measurement method is used, where an electrical quantity, the operational amplifier output voltage, varies in accordance to the variation of the quantity of interest, in such a way that the electrical quantity compensates the effect of the former in the sensor. In our case, the quantity to be measured is the speed of the wind and the quantity of substitution is operational amplifier output voltage. Studies were carried out considering two types of sensors, the metallic PTC and the thermistor NTC. An analysis of the measurement circuits was carried out for each sensor type, taking into account the constants and variables that influence the measurement process. For these circuits, simulation results are presented which make possible to evaluate the measurement system behavior. An analysis of the sensitivity of the measurement circuits output voltage with respect to the wind speed is also carried out. This analysis made possible the development of a procedure for determining the operation point for the NTC-based circuit that yields the maximum sensitivity. From the analysis of the measurement configurations sensitivity, it was observed that the NTC-based configuration presents higher sensitivity compared to the PTC-based configuration, for relatively low operating temperatures, above the ambient temperature. The equivalent sensitivity for the PTC-based configuration occurs only for temperatures much higher than that for achieving the maximum sensitivity for the NTC. This characteristic can be used for implementing anemometers that operates at a temperature much closer to the ambient temperature.